Pengetahuan Asma: Pengaruh Pemberian Buku Edukasi Asma Terhadap Peningkatan Pengetahuan Guru-guru Sekolah Dasar - KHAIRUNNISA KHAIRUNNISA; HARI RONALDO TANJUNG (Fakultas Farmasi Universitas Pancasila, 2014)
The knowledge of teachers on asthma and its managements are very important, in order that teachers can provide the assistance required by the students in primary school who suffered an asthma attack while at school. This study aimed to examine the effect of an educational book to improve knowledge among primary school teachers on asthma and its management. This study was descriptive study, using questionnaires and educational book “Asthma: The Role of Teachers in the Management of Asthma in Schools”. The research was conducted in 3 phases: (1) asses the knowledge of teachers on asthma before being given an educational book, (2) administration of an educational book “Asthma: The Role of Teachers in the Management of Asthma in Schools”, (3) re-asses the knowledge of teachers on asthma after administration an educational book. A total of 48 teachers from three primary schools in the Medan Deli District involved in the study. In general, their knowledge of asthma before being given education is fairly low. After administering education the teacher knowledge increased, this can be seen from the increase in the number of teachers who answered correctly on any given question. An increase of almost 30% of teachers who correctly answer to questions about the causes of asthma after booklet administration and about 20% for questions about symptoms, and treatment of asthma. It can be concluded that the educational materials such as educational book has the effect to increase the knowledge of teachers about asthma and its treatment. It can be seen from the existence of increase in the number of teachers who answered correct on every the question given. This study concluded that the educational book entitle “Asthma: The Role of Teachers in the Management of Asthma in Schools “ has effective to improve knowledge among primary school teachers on asthma and its managements.